2022
DOI: 10.1177/15569845221137898
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Coronary Artery Bypass Grafting in a Patient With Chronic Tracheostoma: Alternative to Reduce Sternal Wound Complication Risk

Abstract: Patients with chronic tracheostoma present a challenge when they require coronary bypass surgery due to an elevated risk of sternal wound infections (SWI). Minimally invasive coronary artery bypass grafting (MICS CABG) is a robust technique that allows complete surgical revascularization while mitigating the risks of sternal complications and functional decline associated with sternotomy. In such patients at elevated risk for SWI, MICS CABG may represent a viable revascularization strategy to avoid sternotomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Guo et al also reported functional outcomes to supplement and strengthen the investigated clinical outcomes [18] . Of the patients who completed the questionnaire, 12 (2.8%) had > CCS Class II angina and 19 (4.5%) reported having > NYHA Class II symptoms.…”
Section: Functional Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Guo et al also reported functional outcomes to supplement and strengthen the investigated clinical outcomes [18] . Of the patients who completed the questionnaire, 12 (2.8%) had > CCS Class II angina and 19 (4.5%) reported having > NYHA Class II symptoms.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Additionally, MICS CABG is employed in cases of left main coronary artery disease with normal right coronary artery disease, previous unsuccessful PCIs, triple vessel disease with medium to large PDA or left ventricular branch of the RCA, and complex proximal left-sided lesions in the presence or absence of main branch involvement [17] . Patients with less diffuse coronary artery may elect to undergo MICS CABG due to its reduced invasiveness and improved functional outcomes [18] . Furthermore, for patients who are at high risk of complications related to sternotomy, such as those with chronic tracheostoma or diabetes [5,19] , MICS CABG could be an attractive alternative.…”
Section: Indicationsmentioning
confidence: 99%
See 3 more Smart Citations